ARS Conceptual Framework for AI-Driven Systematic Reviews in Sports Science and Medicine - Tiago Fernandes; Marta Castañer; Oleguer Camerino (Apunts: Educación Física y Deportes)
Sports coaching and medical teams require valuable, accessible information to support their practices, and systematic reviews offer a well-established, trusted method of producing synthesised evidence to inform their decision-making. However, it entails significant costs due to the required time and human resources, while immediate and systematic evidence synthesis methods remain scarce. Despite the recent advances in machine learning and natural language processing in making information task automation viable, a notable gap seems to exist in their integration and within the principles of the scientific method. Therefore, this scientific note presents the structure and conceptualisation of a proposed framework to automate the workflow of systematic reviews, illustrated through an early implementation within a web application, namely Automatic Research Synthesis (ARS), intending to reduce the time and effort required by researchers and practitioners in sports science and medicine.